Influence of rainfall variability on bean production (Phaseolus vulgaris L.) in a municipality of Brazilian semiarid - Batista, Mateus Costa; Santos, João Paulo de Oliveira; Silva Filho, José Adalberto da; Sousa, João Ítalo de; Félix, Rodolfo José da Silva; Silva, José Luiz Carneiro da (Journal of Environmental Analysis and Progress, 2018)
Brazilian semiarid region is marked by the constant incidence of droughts periods, which are climatic events responsible for great disorders for agricultural production, an activity traditionally based on subsistence agriculture. The study aimed at analyzing the evolution of bean production in the municipality of Itaporanga, Paraíba State, Brazil, between 2005-2015, associating these results with local rainfall. It was performed the Principal Component Analysis. Six years of the 11-year series presented a value of annual precipitation lower than the historical mean of the municipality (838 mm). The crop area with beans in the municipality ranged from 5,560 hectares in 2006 to 150 hectares in 2013. There were large variations in the amount of bean production, with values ranging from 2 to 1,985 tons. The PCA recorded a value of 92.4% of explanation in the first two axes and demonstrated a strong correlation between the analyzed variables with the precipitation. Confirming that proper pluviometric indexes are determining factors on bean production in Itaporanga, Paraíba State, Brazil.